An in vivo evaluation of an lontophoretic Technique for increasing the surface fluoride content in enamel - Barbakow, F. H.; van der Merwe, E. H. M.; Scanes, S. G.; et al (My University, 1973)
Surface enamel fluoride concentrations were determined in IS subjects before and after topical fluoride applications. These IS subjects were divided into 2 groups, one of which received the fluoride applications iontophoreti- cally whereas the control group had the identical fluoride applications without the use of the current. The results indicate that the greatest increase in fluoride concentrations resulted after 3 applications done at weekly intervals when the iontoplioretic technique was employed. Two iontophoretic fluoride applications with an interval of a week between them resulted in a less marked increase whereas no increase was observed when fluoride was applied once only. The increase in the fluoride concentration of the surface enamel was not as significant when the fluoride was applied without the use of current.
KIM
Keywords: Dental Enamel; Fluorides